Cluster-based multi-hop vehicular communication with multi-metric optimization - Alawi, Mahmoud; Saeed, Rashid Abdelhaleem; Hassan Abdalla Hashim, Aisha (2012)
Dead spot and out of coverage problem are serious problems especially in the rural and suburban areas where the network infrastructure is not deployed. In this paper, a new end to end multi hop relay scheme for vehicular communication is proposed to extend the coverage or/and relaxing frequent handoff process. The scheme allows vehicles to continue connected to infrastructure network i.e. UMTS. Relay discovery, relay selection and gateway selection are discussed and examined. The proposed scheme can be implemented on top of any VANET routing protocols. AODV and DSDV were used as underlying protocol to evaluate our scheme. An integrated simulation environment combined of VanetMobiSim and NS2 is used to simulate our proposed scheme. The simplified gateway selection shows the best performance on top of AODV compare to DSDV.